M6A demethylase ALKBH5 drives denervation‐induced muscle atrophy by targeting HDAC4 to activate FoxO3 signalling. Issue 2 (9th February 2022) - Liu, Yuantong; Zhou, Tianjian; Wang, Qinghe; Fu, Runhan; Zhang, Zengfu; Chen, Nandi; Li, Zhizhong; Gao, Guoyong; Peng, Songlin; Yang, Dazhi
Abstract: Background: Skeletal muscle atrophy is a common clinical manifestation of various neurotrauma and neurological diseases. In addition to the treatment of primary neuropathies, it is a clinical condition that should be investigated. FoxO3 activation is an indispensable mechanism in denervation‐induced muscle atrophy; however, upstream factors that control FoxO3 expression and activity have not been fully elucidated. N 6 ‐methyladenosine (m 6 A) methylation is a novel mode of epitranscriptional gene regulation that affects several cellular processes. However, the biological significance of m 6 A modification in FoxO3‐dependent atrophy is unknown. Methods: We performed gain‐of‐function and loss‐of‐function experiments and used denervation‐induced muscle atrophy mouse model to evaluate the effects of m 6 A modification on muscle mass control and FoxO3 activation. m 6 A‐sequencing and mass spectrometry analyses were used to establish whether histone deacetylase 4 (HDAC4) is a mediator of m 6 A demethylase ALKBH5 regulation of FoxO3. A series of cellular and molecular biological experiments (western blot, immunoprecipitation, half‐life assay, m 6 A‐MeRIP‐qPCR, and luciferase reporter assays among others) were performed to investigate regulatory relationships among ALKBH5, HDAC4, and FoxO3. Results: In skeletal muscles, denervation was associated with a 20.7–31.9% decrease in m 6 A levels ( P  < 0.01) and a 35.6–115.2% increase in demethylase ALKBH5 protein levels ( P  < 0.05). Overexpressed ALKBH5 reduced m 6 A levels, activated FoxO3 signalling, and induced excess loss in muscle wet weight (−10.3% for innervation and −11.4% for denervation, P  < 0.05) as well as a decrease in myofibre cross‐sectional areas (−35.8% for innervation and −33.3% for denervation, P  < 0.05) during innervation and denervation. Specific deletion of Alkbh5 in the skeletal muscles prevented FoxO3 activation and protected mice from denervation‐induced muscle atrophy, as evidenced by increased muscle mass (+16.0%, P  < 0.05), size (+50.0%, P  < 0.05) and MyHC expression (+32.6%, P  < 0.05). Mechanistically, HDAC4 was established to be a crucial central mediator for ALKBH5 in enhancing FoxO3 signalling in denervated muscles. ALKBH5 demethylates and stabilizes Hdac4 mRNA. HDAC4 interacts with and deacetylates FoxO3, resulting in a significant increase in FoxO3 expression (+61.3–82.5%, P  < 0.01) and activity (+51.6–122.0%, P  < 0.001). Conclusions: Our findings elucidate on the roles and mechanisms of ALKBH5‐mediated m 6 A demethylation in the control of muscle mass during denervation and activation of FoxO3 signalling by targeting HDAC4. These results suggest that ALKBH5 is a potential therapeutic target for neurogenic muscle atrophy.